Application of Pursed-Lip Breathing in a Patient with Right-sided Pneumothorax (Pneumothorax Dextra): a Case Report - Nur'aeni, Yuni; Sari, Eka Afrima; Platini, Hesti (CV. Literasi Publikasi Indonesia, 2025)
Pneumothorax is a condition in which air enters the pleural cavity of the lungs, potentially disrupting the respiratory process. A common clinical manifestation is severe shortness of breath during inspiration. Pursed-lip breathing is a non-pharmacological therapy that can relax the respiratory muscles and reduce dyspnea. This study aims to examine the application of pursed-lip breathing in a patient with pneumothorax and its effect on respiratory status. Mr. X, a 70-year-old fisherman, was admitted to the hospital with complaints of severe shortness of breath and difficulty breathing. The patient was medically diagnosed with right-sided pneumothorax due to ruptured bleb, suspected to be caused by chronic active pulmonary tuberculosis. A chest tube thoracostomy (CTT) procedure had been performed. The patient had a 55-year history of smoking 1.5-2 packs of cigarettes per day. This case report employed a nursing care approach. The intervention administered was pursed-lip breathing, conducted over three days with three repetitions per session. The evaluation focused on respiratory rate, oxygen saturation, and the level of dyspnea based on the Modified Borg Scale and the Modified Medical Research Council (mMRC) Dyspnea Scale. Evaluation results showed a decrease in respiratory rate from 25 to 21 breaths per minute and an increase in oxygen saturation from 94% to 97%. Additionally, dyspnea severity decreased from a Borg score of 3 to 2 and from mMRC grade 2 to grade 1 following the intervention. Pursed-lip breathing can improve respiratory status and reduce dyspnea, suggesting its potential as a non-pharmacological therapy for patients with pneumothorax.